Daniel Pitín - Blind man's buff - Price, Matt; Budak, Adam 1966- (Hatje Cantz, 2015)
In his painterly work, Daniel Pitín (*1977 in Prague), a leading figure among a generation of artists to have emerged since the fall of communism in Central and Eastern Europe, explores political, architectural, and psychological dystopias through subjects including espionage and surveillance, cinematography and theater sets, pornography and loneliness. Distinctively melancholic though hauntingly beautiful scenes blur the boundaries between figuration and abstraction. Pitíns practice can also be described as expanded painting, regularly exploring collage, film, and installation as means to go beyond the canvas in his journey into Europes recent communist past and into the minds and hearts of those who lived through it